2016
DOI: 10.1111/1471-3802.12293
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Support for Inclusion

Abstract: Nowadays, in Catalonia, students with autism spectrum disorders (ASD) are increasingly in regular schools although their presence, participation, learning and success are unequal. Barriers towards inclusion often depend on how to organise supporting at regular schools and the teachers’ collaboration during this process. In this paper, the support management and teachers’ collaboration of four schools (three in primary and one in secondary education), from the surrounding of Barcelona, are analysed. Through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In addition, the researchers found that teachers emphasized the need for versatile professional development to be available when needs arise. Sanahuja-Gavaldà et al ( 2016 ) reported that barriers to inclusion often depend on how the school organizes support and teacher cooperation during this process. Schlieder et al ( 2014 ) reported that the large increase in the number of children with ASD affects inclusion in mainstream schools, and that there is a need for teachers who are skilled in evidence-based methods to support pupils with ASD.…”
Section: Previous Research On Pupils With Asdmentioning
confidence: 99%
“…In addition, the researchers found that teachers emphasized the need for versatile professional development to be available when needs arise. Sanahuja-Gavaldà et al ( 2016 ) reported that barriers to inclusion often depend on how the school organizes support and teacher cooperation during this process. Schlieder et al ( 2014 ) reported that the large increase in the number of children with ASD affects inclusion in mainstream schools, and that there is a need for teachers who are skilled in evidence-based methods to support pupils with ASD.…”
Section: Previous Research On Pupils With Asdmentioning
confidence: 99%
“…However, it´s necessary have support well systematized that facilitate the development of the learning of students with ASD, deepening all the factors that influence meaningful teachinglearning [17]. This systemic interaction is developed through intersection of inherent thought process, which is linked to a semantic-pragmatic process about its own functioning dynamics, through which it´s understood and, finally, encoded [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, important to promote teachers' confidence in the abilities of self-regulatory learning of all pupils, recognizing their uniqueness, while treating difficulties as barriers that are overcome by the universal modeling of educational processes [36,37]. In this manner, support for pupils with special educational needs is transferred from specialized classrooms to general classrooms, strengthening the role of teacher support through the modeling of the educational process and cooperation with specialists [38]. Teachers, by preventively anticipating possible barriers to pupils' learning in the educational process, make planned adaptations to the educational process and implement them not through individual intervention but by treating these adaptations as an integral part of the lesson plan [39].…”
Section: Literature Reviewmentioning
confidence: 99%